Clinical and morphological parallels in the validation of surgical treatment of nephrotuberculosi - Novikov, B I; Skornyakov, S N; Berdnikov, R B; Savelev, A V (Urologii͡a︡ (Moscow, Russia : 1999), 2016)
To Study clinical and morphological variants of kidney tuberculosis (KTB), for grounding a tactics of surgical treatment. There were 107 examined patients (patients with cavitary lesions of kidneys: cavernous and multi-cavernous), operated in different phases of KTB. There were 56 men (52,3%) and women - 51(47,7%). The mean age of patients was 57,6 years (23-84 years). All the patients had a complex examination, including X-ray and ultrasound investigations, computer tomography ( was performed selectively), bacteriological examinations of urine and morphological examinations of removed kidneys or their parts. Surgical interventions were as follows: open surgery nephrectomy 86/107 (80,4%), open organ-sparing surgery (resections of kidneys) 21/107 ( 19,6%). Mycobacterium tuberculosis were revealed by cultural method in 68,6% of cases in patients with cavernous KTB and in 76,3% of cases in patients with multi-cavernous KTB. In appliance with pathomorphological results of presented specimens, there were revealed 3 groups, each one with its own properties of cavern wall. I group (74 specimens) - stage of active progressing KTB, II group (20 specimens) - stage of intermediate activity, III group (13 specimens) - stage of healed caverns. Performed morphological investigations allowed us grounded a rational tactics of surgical treatment. It was defined that the longer specific anti-TB therapy was carried out the less frequency of TB progression we would have. However when it presented isolated cavitary lesion (isolated cavern), the performance of adequate and long courses of chemotherapy is not worth to do. Only surgical interventions (resection of infected tissue) with the anti-TB therapy allowed to reach the satisfactory results in treatment of KTB.